Priming effect of colour on aiding the attentional reorientation in sequential presentations of temporal data vizualisation: evidence from eye-tracking. (11th January 2022) - Peng, Ningyue; Xue, Chengqi; Wang, Haiyan; Niu, Yafeng; Wu, Lei
Abstract: The paper by Ningyue Peng, Chengqi Xue, Haiyan Wang, Yafeng Niu and Lei Wu, published in Interacting with Computers (August 2021), explores the use of colour to influence behavioural performance using eye-tracking.